Methodological foundations of the modern training system of skilled handballers - V.A. Tyshchenko (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose: to consider the direction of training handball team in the annual Ukrainian Superleague macrocycles game seasons in years 2006-2013. Material: in the experiment took part 125 participated highly qualified handballers. The analysis of more than 50 references on multi-year training athletes is conducted. Results: confirmed advisability of constructing the training process handball qualifications based on the structural components of the preparation. According to the requirements of the system approach presented technology of preparation are disclosed management methodology training process in terms of long-term training. Conclusions: it is necessary to compile and optimize long-term training program handball qualifications; raise the level of preparedness of the various parties in strict accordance with the objective laws of the formation of their constituents, and calendar events, to consider specific features of the occurrence of adaptive reactions in improving the various components of sportsmanship.